A multifunctional polyimide / nano-silicon composite negative electrode material and its preparation method and application
By using multifunctional polyimide/nano-silicon composite anode material in lithium-ion batteries, the performance degradation caused by volume expansion of the silicon anode during charging and discharging is solved, and good cycle stability and rate performance are achieved, and the performance of the silicon anode is avoided. The use of secondary binder reduces the production cost and simplifies the process.
Patent Information
- Application Number
- CN202210072392.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-21
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-01-21
AI Technical Summary
The volume expansion of the silicon negative electrode in lithium-ion batteries during charging and discharging leads to poor capacity attenuation, cycle stability and rate performance, and the prior art requires the addition of secondary binder.
Using multifunctional polyimide/nanosi composite anode material, a stable SEI film is formed by coating the polyimide layer on the nano-silicon surface, and the good mechanical properties and bonding properties of multifunctional polyimide are utilized. Avoid the use of secondary binders.
The cyclic stability and rate performance of the silicon negative electrode are improved, the electrode preparation cost is reduced, the process flow is simplified, and mechanical stability is provided to resist volume expansion during charging and discharging.
Smart Images

Figure CN114373919B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a multifunctional polyimide / nano-silicon composite negative electrode material and a preparation method and application thereof. Background Art
[0002] Silicon is widely considered to be the most promising negative electrode material for lithium-ion batteries due to its high theoretical specific capacity (4200mAh / g), low charge and discharge platform and abundant reserves in nature. However, silicon negative electrodes have an inevitable problem in practical applications. Due to the huge volume expansion of silicon negative electrodes during the charge and discharge process, the capacity of silicon negative electrodes decays rapidly, and has poor cycle stability and rate performance. Polyimide is a common engineering plastic that has been widely used in many advanced technical fields by virtue of its excellent thermal stability, low dielectric constant and excellent mechanical and mechanical properties. It is a class of polymers containing functional imide groups. The difference from other high-performance polymers is that it can be prepared into uniform films and quantitatively converted into polyimide (PI) by relying on the solubility of the precursor polyamic acid (PAA), which is a promising green and renewable alternative to fossil fuels. The most common PI is aromatic polyimide, which has excellent mechanical properties, low temperature resistance, electron radiation resistance, dielectric properties, green environmental protection, thermal stability, mechanical properties (such as low creep and high strength), chemical resistance and high thermal expansion coefficient. Aromatic PI contains a rigid molecular structure in its macromolecular skeleton. Due to its excellent physical properties, it is now widely used in circuit electronics, aerospace, and automotive industries. Amines and imides can be properly and effectively designed to obtain the best molecular structure, thereby applying polyimide to various fields. At present, there have been reports on the use of polyimide as an active material or binder in lithium-ion batteries, but there is almost no research on multifunctional polyimide. The research on this multifunctional polyimide will provide new ideas for the application and research of silicon negative electrodes in lithium-ion batteries. Summary of the invention
[0003] In view of the shortcomings of the prior art, the present invention aims to provide a multifunctional polyimide / nano-silicon composite negative electrode material and its preparation method and application. The multifunctional polyimide can be used as a binder, coating material and active material in the preparation process of lithium-ion battery silicon negative electrode, eliminating the need for the addition of secondary binder.
[0004] The purpose of the present invention is achieved through the following technical solutions:
[0005] A method for preparing a multifunctional polyimide / nano-silicon composite negative electrode material comprises the following steps:
[0006] (1) dispersing nano-silicon in an organic solution to obtain a uniformly dispersed nano-silicon dispersion;
[0007] (2) adding an equimolar ratio of a polymerizable monomer and terephthalamide (TA) to the nano-silicon dispersion described in step (1) to obtain a reactant, wherein the polymerizable monomer is at least one of pyromellitic dianhydride (PMDA), 3,4,9,10-perylenetetracarboxylic dianhydride (PTCDA) and 1,4,5,8-naphthalenetetracarboxylic anhydride (NDA); heating the reactant in an oil bath to carry out a polymerization reaction, vacuum drying and grinding the reaction liquid after the polymerization reaction, and then calcining and grinding again under a protective gas atmosphere to prepare the multifunctional polyimide / nano-silicon composite negative electrode material.
[0008] Preferably, the particle size of the nano-silicon in step (1) is 30 to 60 nm.
[0009] Preferably, the concentration of the nano-silicon dispersion in step (1) is 3.3-10 mg / mL.
[0010] Preferably, the organic solution in step (1) is at least one of N-methylpyrrolidone, dimethyl sulfoxide and N,N-dimethylformamide.
[0011] Preferably, the polymerization reaction temperature in step (2) is 120-200°C, more preferably 180°C.
[0012] Preferably, the polymerization reaction time in step (2) is 6 to 12 hours, more preferably 10 hours.
[0013] Preferably, the vacuum drying in step (2) is performed at 100-200° C. for 6-12 h, more preferably at 140° C. for 8 h.
[0014] Preferably, the vacuum drying and grinding time in step (2) is 0.5 h; the calcination and re-grinding time under a protective gas atmosphere is 0.5 h.
[0015] Preferably, the protective gas atmosphere in step (2) is an inert gas or nitrogen.
[0016] Preferably, the calcination method in step (2) is: heating to 300-350°C at a heating rate of 5-20°C / min and keeping warm for 6-12h; more preferably: heating to 300°C at a heating rate of 5°C / min and keeping warm for 8h.
[0017] The multifunctional polyimide / nano-silicon composite negative electrode material is prepared by the method for preparing the multifunctional polyimide / nano-silicon composite negative electrode material.
[0018] The application of the above multifunctional polyimide / nano-silicon composite negative electrode material in the preparation of negative electrode materials for lithium-ion batteries.
[0019] The present invention achieves the purpose of ensuring good cycle stability of silicon negative electrode and avoiding the use of secondary binder through the following three approaches. First, by coating a uniform polyimide coating on the surface of nano silicon, direct contact between nano silicon and electrolyte is avoided to form a stable SEI film. In addition, this multifunctional polyimide has good mechanical properties and can withstand the huge volume expansion of silicon during the charging and discharging process, thereby improving the cycle stability of silicon negative electrode. Second, this multifunctional polyimide itself also has the potential to be used as a lithium ion battery, and its theoretical specific capacity reaches 1704mAh / g. Therefore, the good electrochemical properties of the multifunctional polyimide itself can also enable it to play the role of active material in the composite negative electrode material. Third, in the preparation process of this multifunctional polyimide / nano silicon composite negative electrode material, due to the good bonding properties of this multifunctional polyimide itself, there is no need to add secondary binder in the later electrode sheet preparation process, which not only saves costs but also simplifies the electrode sheet preparation process.
[0020] Compared with the prior art, the beneficial effects of the present invention include:
[0021] (1) The advantage of the present invention is that the stable multifunctional polyimide coating formed on the surface of nano-silicon has good mechanical properties and electrical conductivity, which can not only resist the huge volume expansion of the silicon negative electrode during the charging and discharging process, but also has good electronic conductivity, which can improve the rate performance of the silicon negative electrode. More importantly, the good bonding performance of the multifunctional polyimide itself can eliminate the need for the addition of secondary binders in the later electrode sheet preparation process, which not only reduces the electrode preparation cost, but also simplifies the electrode preparation process. In addition, this multifunctional polyimide also helps to form a stable SEI film on the surface of the silicon negative electrode, thereby improving the cycle stability of the silicon negative electrode. We have combined the multiple functions of this multifunctional polyimide to prepare a multifunctional polyimide / nano-silicon composite negative electrode with many advantages such as good cycle stability, outstanding rate performance, low preparation cost, and simple preparation process.
[0022] (2) The multifunctional polyimide / nano-silicon composite negative electrode prepared by the present invention greatly improves the cycle stability of the silicon negative electrode during the charge and discharge process due to the stable coating layer formed by the multifunctional polyimide on the surface of the nano-silicon and the good mechanical stability and bonding properties of the multifunctional polyimide itself. At the same time, since the multifunctional polyimide / nano-silicon composite negative electrode eliminates the need for adding a secondary binder during the electrode preparation process, this can simplify the electrode preparation process and save costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the infrared spectrum of the multifunctional polyimide / nano-silicon composite negative electrode material prepared in Example 1.
[0024] Figure 2This is a cycle performance diagram of the multifunctional polyimide / nano-silicon composite negative electrode material prepared in Example 4 when used as the negative electrode of a lithium-ion battery.
[0025] Figure 3 This is a SEM image of the multifunctional polyimide / nano-silicon composite negative electrode material prepared in Example 2.
[0026] Figure 4 This is a SEM image of the multifunctional polyimide / nano-silicon composite negative electrode material prepared in Comparative Example 1.
[0027] Figure 5 These are stress-strain diagrams of the multifunctional polyimide / nano-silicon composite negative electrode material, PVDF / nano-silicon and CMC / SBR / nano-silicon prepared in Example 1. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0029] Example 1
[0030] A method for preparing a multifunctional polyimide / nano-silicon composite negative electrode material, comprising the following steps:
[0031] (1) 100 mg of nano-silicon and 30 ml of N-methylpyrrolidone were ultrasonicated in a round-bottom flask for 2 h, and then stirred for 2 h. The reaction temperature was room temperature, so that the nano-silicon was uniformly dispersed in the solvent;
[0032] (2) adding 3 mmol PMDA and 3 mmol TA which had been dried to the dispersion obtained in step (1), and stirring at room temperature for 2 hours;
[0033] (3) transferring the reaction solution obtained in step (2) to an oil bath and reacting at high temperature for 10 hours at a reaction temperature of 180° C.;
[0034] (4) transferring the mixed solution obtained after the reaction in step (3) into an evaporating dish, and then placing it in a vacuum drying oven for vacuum drying for 8 hours at a drying temperature of 140° C.;
[0035] (5) grinding the solid obtained in step (4) in a mortar for 0.5 hours, and then sintering in a tube furnace at a heating rate of 5°C / min to 300°C for 8 hours under a nitrogen atmosphere;
[0036] (6) Grinding the solid particles obtained in step (5) again for 0.5 hours to obtain the multifunctional polyimide / nano-silicon composite negative electrode material.
[0037] Example 2
[0038] A method for preparing a multifunctional polyimide / nano-silicon composite negative electrode material, comprising the following steps:
[0039] (1) 200 mg of nano-silicon and 30 ml of dimethyl sulfoxide were ultrasonicated in a round-bottom flask for 2 h, and then stirred for 2 h. The reaction temperature was room temperature, so that the nano-silicon was evenly dispersed in the solvent;
[0040] (2) adding 3 mmol PMDA and 3 mmol TA which had been dried to the dispersion obtained in step (1), and stirring at room temperature for 2 hours;
[0041] (3) transferring the reaction solution obtained in step (2) to an oil bath and reacting at high temperature for 6 hours at a reaction temperature of 120° C.;
[0042] (4) transferring the mixed solution obtained after the reaction in step (3) into an evaporating dish, and then placing it in a vacuum drying oven for 6 hours at a drying temperature of 100° C.;
[0043] (5) grinding the solid obtained in step (4) in a mortar for 0.5 hours, and then sintering in a tube furnace at a heating rate of 10°C / min to 350°C for 6 hours under a nitrogen atmosphere;
[0044] (6) Grinding the solid particles obtained in step (5) again for 0.5 hours to obtain the multifunctional polyimide / nano-silicon composite negative electrode material.
[0045] Example 3
[0046] A method for preparing a multifunctional polyimide / nano-silicon composite negative electrode material, comprising the following steps:
[0047] (1) 300 mg of nano-silicon and 30 ml of N-methylpyrrolidone were ultrasonicated in a round-bottom flask for 2 h, and then stirred for 2 h. The reaction temperature was room temperature, so that the nano-silicon was uniformly dispersed in the solvent;
[0048] (2) adding 3 mmol PMDA and 3 mmol TA which had been dried to the dispersion obtained in step (1), and stirring at room temperature for 2 hours;
[0049] (3) transferring the reaction solution obtained in step (2) to an oil bath and reacting at high temperature for 8 hours at a reaction temperature of 140° C.;
[0050] (4) transferring the mixed solution obtained after the reaction in step (3) to an evaporating dish, and then placing it in a vacuum drying oven for vacuum drying for 10 hours at a drying temperature of 120° C.;
[0051] (5) grinding the solid obtained in step (4) in a mortar for 0.5 h, and then sintering in a tube furnace at a heating rate of 15 °C / min to 350 °C for 10 h under a nitrogen atmosphere;
[0052] (6) Grinding the solid particles obtained in step (5) again for 0.5 hours to obtain the multifunctional polyimide / nano-silicon composite negative electrode material.
[0053] Example 4
[0054] (1) 300 mg of nano-silicon and 30 ml of N-methylpyrrolidone were ultrasonicated in a round-bottom flask for 2 h, and then stirred for 2 h. The reaction temperature was room temperature, so that the nano-silicon was uniformly dispersed in the solvent;
[0055] (2) adding 3 mmol of pyromellitic anhydride and 3 mmol of terephthalamide which had been dried to the dispersion obtained in step (1), and stirring at room temperature for 2 hours;
[0056] (3) transferring the reaction solution obtained in step (2) to an oil bath for high temperature reaction for 12 hours at a reaction temperature of 200° C.;
[0057] (4) transferring the mixed solution obtained after the reaction in step (3) to an evaporating dish, and then placing it in a vacuum drying oven for vacuum drying for 10 hours at a drying temperature of 140° C.;
[0058] (5) grinding the solid obtained in step (4) in a mortar for 0.5 hours, and then sintering in a tube furnace at a heating rate of 10°C / min to 350°C for 12 hours under a nitrogen atmosphere;
[0059] (6) Grinding the solid particles obtained in step (5) again for 0.5 hours to obtain the multifunctional polyimide / nano-silicon composite negative electrode material.
[0060] Comparative Example 1
[0061] (1) 500 mg of nano-silicon and 30 ml of N,N-dimethylformamide were ultrasonicated in a round-bottom flask for 2 h, and then stirred for 2 h. The reaction temperature was room temperature, so that the nano-silicon was evenly dispersed in the solvent;
[0062] (2) adding 3 mmol of pyromellitic anhydride and 3 mmol of terephthalamide which had been dried to the dispersion obtained in step (1), and stirring at room temperature for 2 hours;
[0063] (3) transferring the reaction solution obtained in step (2) to an oil bath and reacting at high temperature for 10 hours at a reaction temperature of 160° C.;
[0064] (4) transferring the mixed solution obtained after the reaction in step (3) into an evaporating dish, and then placing it in a vacuum drying oven for vacuum drying for 8 hours at a drying temperature of 160° C.;
[0065] (5) grinding the solid obtained in step (4) in a mortar for 0.5 hours, and then sintering in a tube furnace at a heating rate of 20°C / min to 450°C for 12 hours under a nitrogen atmosphere;
[0066] (6) Grinding the solid particles obtained in step (5) again for 0.5 hours to obtain the multifunctional polyimide / nano-silicon composite negative electrode material.
[0067] Figure 1 This is the infrared spectrum of the multifunctional polyimide / nano-silicon composite negative electrode material prepared in Example 1. Figure 1 It can be seen that the amide functional groups exist stably when polyimide is synthesized alone and when the polyimide / silicon composite material is synthesized, indicating the successful synthesis of multifunctional polyimide on the silicon surface.
[0068] The method for synthesizing polyimide alone is as follows: 3 mmol PMDA and 3 mmol TA that have been dried are added to 30 ml N,N-dimethylformamide, stirred at room temperature for 2 hours to obtain a reaction solution, and the reaction solution is transferred to an oil bath pot for high-temperature reaction for 10 hours at a reaction temperature of 180°C.
[0069] Figure 2 The multifunctional polyimide / nano-silicon composite negative electrode material prepared in Example 4 is used as a negative electrode of a lithium-ion battery. Figure 2 It can be seen that the multifunctional polyimide / nano-silicon composite negative electrode material prepared by the present invention has good electrochemical properties, indicating that the multifunctional role of the multifunctional polyimide in the silicon negative electrode is reflected.
[0070] The steps for preparing lithium-ion batteries are as follows:
[0071] (1) Weigh 70 mg of the multifunctional polyimide / silicon composite negative electrode material prepared in step (6) and 30 mg of conductive carbon black, and grind them in a mortar for 1 hour:
[0072] (2) adding the powder sample ground in step (1) into a small beaker and adding 450 μL of N-methylpyrrolidone, and stirring the mixed slurry for 12 hours;
[0073] (3) coating the slurry prepared in step (2), wherein the coating material is copper foil with a thickness of 90 μm;
[0074] (4) placing the electrode sheet coated in step (3) in a vacuum drying oven and drying for 12 hours at a drying temperature of 70° C.;
[0075] (5) using a punching machine to press the electrode sheet dried in step (4) into a circular electrode sheet with a diameter of 1 cm;
[0076] (6) The electrode sheet prepared in step (5) is assembled into a CR2016 battery, wherein the positive electrode material is a lithium sheet, the electrolyte is an electrolyte formed by dissolving 1 mol LiPF6 in an EC / DMC / EMC solution with a volume ratio of 1:1:1, and the separator is Celgard 2500.
[0077] Test conditions: Let the assembled battery stand for 6 hours before testing. Test voltage: 0~3V, test current: 0.1A~5A.
[0078] Figure 3 is a SEM image of the multifunctional polyimide / nano-silicon composite negative electrode material prepared in Example 2; Figure 3 It can be seen that the surface of the nano-silicon particles is evenly coated and bonded together by the multifunctional polyimide without agglomeration. This stable coating structure is beneficial to improving the cycle stability of the silicon negative electrode during the charge and discharge process.
[0079] Figure 4 This is a SEM image of the multifunctional polyimide / nano-silicon prepared in Comparative Example 1; Figure 4 This indicates that when the silicon content and sintering temperature are too high, the multifunctional polyimide will be unevenly coated on the surface of nano-silicon.
[0080] Figure 5 The stress-strain diagrams of the multifunctional polyimide / nano-silicon composite negative electrode material, PVDF / nano-silicon and CMC / SBR / nano-silicon prepared in Example 1; wherein MF-PI corresponds to Example 1. Figure 5 It shows that compared with the traditional binder PVDF and the commonly used binder CMC / SBR for silicon negative electrodes, the multifunctional polyimide has relatively moderate bonding properties.
[0081] Preparation method of PVDF / nanosilicon:
[0082] (1) Weigh 10 mg of PVDF powder into a small beaker, add 450 μL of N-methylpyrrolidone, and stir for 0.5 h;
[0083] (2) Weigh 70 mg of nano-silicon powder and 20 mg of conductive carbon black and grind them in a mortar for 1 hour:
[0084] (3) adding the powder sample ground in step (2) into a small beaker containing dissolved PVDF, and then stirring the mixed slurry for 12 hours;
[0085] (4) coating the slurry prepared in step (3), wherein the coating material is copper foil with a thickness of 90 μm;
[0086] (5) placing the electrode sheet coated in step (4) in a vacuum drying oven and drying for 12 hours at a drying temperature of 70° C.;
[0087] (6) The electrode sheet dried in step (5) was cut into strips with a length of 10 cm and a width of 1 cm, and then the bonding performance was tested using a stretching machine.
[0088] Preparation method of CMC / SBR / nano silicon:
[0089] (1) Weigh 10 mg of CMC (carboxymethyl cellulose) powder into a small beaker, add 20 mg of SBR (styrene-butadiene rubber) and stir for 0.5 hour;
[0090] (2) Weigh 70 mg of nano-silicon powder and 20 mg of conductive carbon black and grind them in a mortar for 1 hour:
[0091] (3) adding the powder sample ground in step (2) into a small beaker in which CMC / SBR is dissolved, and then stirring the mixed slurry for 12 hours;
[0092] (4) coating the slurry prepared in step (3), wherein the coating material is copper foil with a thickness of 90 μm;
[0093] (5) placing the electrode sheet coated in step (4) in a vacuum drying oven and drying for 12 hours at a drying temperature of 70° C.;
[0094] (6) The electrode sheet dried in step (5) was cut into strips with a length of 10 cm and a width of 1 cm, and then the bonding performance was tested using a stretching machine.
[0095] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a multifunctional polyimide / nano-silicon composite negative electrode material, characterized in that: The steps include: (1) dispersing nano-silicon in an organic solution to obtain a uniformly dispersed nano-silicon dispersion; (2) adding an equimolar ratio of a polymerizable monomer and terephthalamide to the nano-silicon dispersion liquid described in step (1) to obtain a reactant, wherein the polymerizable monomer is at least one of pyromellitic anhydride, 3,4,9,10-perylenetetracarboxylic anhydride and 1,4,5,8-naphthalenetetracarboxylic anhydride; heating the reactant in an oil bath to carry out a polymerization reaction, vacuum drying and grinding the reaction liquid after the polymerization reaction, and then calcining and grinding again under a protective gas atmosphere to prepare the multifunctional polyimide / nano-silicon composite negative electrode material, wherein the multifunctional polyimide / nano-silicon composite negative electrode material is prepared by coating the surface of nano-silicon with a uniform polyimide coating; The particle size of the nano-silicon in step (1) is 30-60 nm; the concentration of the nano-silicon dispersion in step (1) is 3.3-10 mg / mL; The temperature of the polymerization reaction in step (2) is 180° C.; the time of the polymerization reaction in step (2) is 10 h; The vacuum drying method of step (2) is: vacuum drying at 100-200° C. for 6-12 hours; the calcination method of step (2) is: heating to 300-350° C. at a heating rate of 5-20° C. / min and keeping the temperature for 6-12 hours.
2. The method for preparing a multifunctional polyimide / nano-silicon composite negative electrode material according to claim 1, characterized in that: The vacuum drying method in step (2) is: vacuum drying at 140° C. for 8 h; the calcination method in step (2) is: heating to 300° C. at a heating rate of 5° C. / min and keeping the temperature for 8 h.
3. The method for preparing a multifunctional polyimide / nano-silicon composite negative electrode material according to claim 1, characterized in that: The time for vacuum drying and grinding in step (2) is 0.5 h; the time for calcining and re-grinding under a protective gas atmosphere is 0.5 h.
4. The method for preparing a multifunctional polyimide / nano-silicon composite negative electrode material according to claim 1, characterized in that: The organic solution in step (1) is at least one of N-methylpyrrolidone, dimethyl sulfoxide and N,N-dimethylformamide; and the protective gas atmosphere in step (2) is an inert gas or nitrogen.
5. The multifunctional polyimide / nano-silicon composite negative electrode material prepared by the method for preparing a multifunctional polyimide / nano-silicon composite negative electrode material according to any one of claims 1 to 4.
6. Use of the multifunctional polyimide / nano-silicon composite negative electrode material according to claim 5 in preparing negative electrode materials for lithium-ion batteries.
Citation Information
Patent Citations
Electrode and preparation method and application thereof
CN111584867A
Polyimide-modified carbon-silicon negative electrode material and preparation method thereof
CN112520719A